Indigenous Sustainable Organic Manuring Practices of Dryland Farmers in Tamil Nadu - Karthikeyan, C.; K, Mohanraj; K , Vijayakumar (Indian Journal of Extension Education, 2013)
The study was undertaken to document various indigenous sustainable organic manuring practices by farmers of Tamil  Nadu. The study was conducted in the selected villages of the dry tracts of Tamil Nadu viz., Coimbatore, Salem, Erode,  Krishnagiri, Dindigul, Villupuram, Ramnad and Virudhunagar districts. Documentation of indigenous sustainable  organic manuring practices was done by direct interview and group discussion methods. Triangulation exercise was also  done in the study village to gather reliable information about indigenous technical knowledge of dry land farmers of Tamil  Nadu. In this paper, important sustainable organic manuring practices adopted by the dry land farmers viz., basal manure  application in coconut, yield improvement in watermelon using tender coconut milk and toddy, composting of dropped  leaves in Guava orchard, cactus as organic manure in coconut, rice husk as manure, rice husk ash as manure and cotton boll  residue as manure in the field were explored and described in detail.
Keywords: Indigenous techniques; organic manuring practice; dryland farmers; documentation